2015
DOI: 10.1063/1.4934986
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the success and failure of mode coupling theory from consideration of entropy

Abstract: We analyze the dynamics of model supercooled liquids in a temperature regime where predictions of mode coupling theory (MCT) are known to be valid qualitatively. In this regime, the Adam-Gibbs (AG) relation, based on an activation picture of dynamics, also describes the dynamics satisfactorily, and we explore the mutual consistency and interrelation of these descriptions. Although entropy and dynamics are related via phenomenological theories, the connection between MCT and entropy has not been argued for. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…However the density range studied here is much higher, thus, predicting that the Rosenfeld relationship is valid over a wider range of densities. Our study also shows that although at low temperatures the WCA system does not follow any density-temperature scaling 21,35,36 , at high temperatures it shows a master plot. The NTW model on the other hand, although is a model of a simple liquid, is known to show characteristics of ionic melts, to be specific the SiO 2 system 26 .…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…However the density range studied here is much higher, thus, predicting that the Rosenfeld relationship is valid over a wider range of densities. Our study also shows that although at low temperatures the WCA system does not follow any density-temperature scaling 21,35,36 , at high temperatures it shows a master plot. The NTW model on the other hand, although is a model of a simple liquid, is known to show characteristics of ionic melts, to be specific the SiO 2 system 26 .…”
Section: Resultsmentioning
confidence: 61%
“…As mentioned in the introduction, the pair entropy S 2 provides 80% − 90% contribution to the excess entropy 4,15,21 and thus, the Rosenfeld relationship can be written in terms of S 2 which is given by,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Thus the crossover temperature from 'normal' to 'slow' dynamics can be treated as a) Electronic mail: mb.sarika@ncl.res.in an onset of slow dynamics 4,9,10 . On further cooling, the system reaches a temperature called mode coupling transition temperature T c , at which the power law behavior of the mode coupling theory (MCT) predicts a divergence of the dynamics 11,12 . Earlier studies have reported that the saddle order nearby extrema of the potential energy surface goes to zero at this temperature [13][14][15][16] , thus connecting a landscape property to the dynamical MCT transition temperature.…”
Section: Introductionmentioning
confidence: 99%